Genetic relationships among Musa spp. as revealed by microsatellite DNA markers - Abdullah, Nur Ashikin Psyquay; Saleh, Ghizan; Wahab, Zakaria (2009)
The present study was conducted to estimate the genetic relationships among 44 Musa genotypes using ten microsatellite markers previously developed from M. acuminata and M. balbisiana. Pairwise similarities between genotypes calculated on the basis of Jaccard’s coefficient ranged between 0.87 to 1.00, indicating the presence of high similarity and thereby low genetic variability among genotypes. In all, nine primers were polymorphic and 195 putative alleles were detected with a mean value of 2.0 per locus. The mean Nei’s gene diversity (h) was 0.1998 with the expected heterozygosity in the total population (HT) being 0.1982, the mean expected heterozygosity in the sub-populations HS being 0.1661 and therefore FST was 0.1618, supporting the fact that there was low genetic variability among genotypes. Dendrogram showed that genotypes were clustered into seven groups but clustering was not dependent on ploidy level.